Efecto del bacillus subtilis y "gallinaza" como supresores de meloidogyne sp. en cultivo capsicum annuum, piura, Perú 2010-2011 - Soto Deza, Nancy Mercedes (2014)
In Piura, Chapairá in plot cultivated Capsicum annuum "chili pepper piquillo" infested with nematodes Meloidogyne sp., the effect of Bacillus subtilis and "chicken manure" was evaluated as suppressing agents knot nematode Meloidogyne sp. Two trials were established, where it is applied design of complete randomized block design. Driveway "chicken manure" was incorporated into 85% pure, at doses 15 and 30 t / ha. For direct sowing seed C. annuum in B. subtilis was inoculated at a concentration of 1X106 spore/mL and 2 X 106 spore/mL. At 45 and 90 days was determined: analysis of nematode populations, nodulation index, plant height, total number of fruits and microbiological analysis to determine the presence of B. subtilis in the wake of C. annuum. The data was subjected to analysis of variance using the Statgraphics plus 5.0 software. Initially, the study showed highly infested knot nema¬tode Meloidogyne sp., 275 to 27720 soil nematodes/100 cm3; after application of B. subtilis, the final population recorded values nematodos/100 13-0 cm3 soil with degree galling index between 0 and 2. The results indicated significant differences (P ≤ 0.05) between treatments. Concluding that the "chicken manure" interacted with B. subtilis favoring suppressive action on Meloidogyne sp. in culture of C. annuum, improving crop productivity.